Intracranial metallic foreign bodies in a man with a headache - Zerrin Pelin; Tuncay Kaner (MDPI AG, 2012)
We report the case of a 22-year old man with intracranial metallic foreign bodies who presented complaining of a headache. His history of headaches had begun when he was five years old and continued with increasing severity. Six months before hospital admission, nausea and vomiting began to accompany his headache. Computed tomography scan revealed that 2 metallic foreign bodies were located adjacent to the vertex and another was next to the ambient cistern. The location and position of foreign bodies suggested that they were introduced in infancy through the anterior fontanelle before its closure in an unsuccessful homicide attempt. This case is one of the few reported cases combining headache and intracranial foreign bodies and we discuss the relationship between headache and these metallic materials.